Serotonin Transporter Genomic Biomarker for Quantitative Assessment of Ondansetron Treatment Response in Alcoholics - Seneviratne, Chamindi; Johnson, Bankole A. (Frontiers in Psychiatry, 2012)
Paucity of sensitive biomarkers to quantify transient changes in alcohol consumption level remains a critical barrier for the development of efficacious therapeutic agents to treat alcoholism. Recently, in an 11-week, randomized, placebo-controlled, double-blind trial of 283 alcohol-dependent individuals, we demonstrated that ondansetron was efficacious at reducing the severity of drinking (measured as drinks per drinking day; DDD) in alcoholics carrying the LL compared with the LS/SS genotype of the serotonin transporter gene, 5′-HTTLPR. Using peripheral blood samples from a cohort of 41 of these subjects, we determined whether there was a relationship between mRNA expression level of the 5′-HTTLPR genotypes (measured at weeks 0, 4, and 11) and self-reported alcohol consumption following treatment with either ondansetron (4 μg/kg twice daily; N = 19) or placebo (N = 22). Using a mixed-effects linear regression model, we analyzed the effects of DDD and 5′-HTTLPR genotypes on mRNA expression levels within and between the ondansetron and placebo groups. We found a significant three-way interaction effect of DDD, 5′-HTTLPR genotypes, and treatment on mRNA expression levels (p = 0.0396). Among ondansetron but not placebo recipients, there was a significant interaction between DDD and 5′-HTTLPR genotype (p = 0.0385 and p = 0.7938, respectively). In the ondansetron group, DDD was associated positively with mRNA levels at a greater rate of expression alteration per standard drink in those with the LL genotype (slope = +1.1698 in ln scale). We suggest that the combination of the LL genotype and 5′-HTTLPR mRNA expression levels might be a promising and novel biomarker to quantify drinking severity in alcoholics treated with ondansetron.